Does the Merger of the Indonesian Islamic Bank Matter for Its Social Mission of Economic Empowerment? - Ainul Fatha Isman; Nur Hidayah (Faculty of Economic and Business, 2024)
Research Originality: Economic empowerment through financing Micro Small Medium Enterprises (MSMEs) is one dimension of the social mission of sharia banking in Indonesia. The merger action of Bank of Sharia Indonesia (BSI) raises the question of whetherthe performance of economic empowerment has changed.Research Objectives: This research aims to analyse the differences in the BSI’s performance of economic empowerment during preand post-merger periods and analyse the issues and strategies for improving BSI's post-merger economic empowerment performance.Research Methods: It is a research using mixed method combining a quantitative explorative analysis approach using Wilcoxon Test, and a qualitative one using Analytic Network Process.Empirical Results: This research finds that BSI's economic empowerment performance has increased in terms of the quantity but decreased in terms of proportion in the post-merger period. ANP research demonstrates that risk management is a priority issue for the BSI post-merger period. The social mission of economic empowerment indicates several priority issues, namely, the relatively higher rate of profit margin than interest, the inadequate supervision model, the low rate of risk management literacy, and the relatively higher risk of profit loss sharing (PLS)-based financing. The strategy analysis indicates that policy intervention for BSI’s MSMEs financing is a top priority in improving the performance of its economic empowerment.Implications: This research recommends some recommendations for sharia banks’ MSMEs financing equivalent to the one of conventional banks. Economic digitalization as technological means to widen accessibility of economic empowerment and distribution segmentation focusing more on the halal sector.JEL Classification: A13, G21, G34How to Cite:Isman, A. F., & Hidayah, N. (2024). Does the Merger of the Indonesian Islamic Bank Matter for Its Social Mission of Economic Empowerment? Etikonomi, 23(2), 333 – 352. https://doi.org/10.15408/etk.v23i2.39810.